Could Arachidonic Acid-Derived Pro-Resolving Mediators Be a New Therapeutic Strategy for Asthma Therapy? - Insuela, Daniella Bianchi Reis; Ferrero, Maximiliano Ruben; Coutinho, Diego de Sá; Martins, Marco Aurélio; Carvalho, Vinicius Frias (Frontiers in Immunology, 2020)
Asthma represents one of the leading chronic diseases worldwide and causes a high global burden of death and disability. In asthmatic patients, the exacerbation and chronification of the inflammatory response are often related to a failure in the resolution phase of inflammation. We reviewed the role of the main arachidonic acid (AA) pro-resolving lipid mediators (PRMs) in the resolution of chronic lung inflammation of asthmatics. AA is metabolized by two classes of enzymes, cyclooxygenases (COX), producing prostaglandins (PGs) and thromboxanes, and lipoxygenases (LOX), forming leukotrienes and lipoxins (LXs). In asthma, two primary pro-resolving derived mediators from COXs are PGE2 and the cyclopentenone prostaglandin15-Deoxy-Delta-12,14-PGJ2 (15d-PGJ2) while from LOXs are the LXA4 and LXB4. In different models of asthma, PGE2, 15d-PGJ2, and LXs reduced lung inflammation and remodeling. Furthermore, these PRMs inhibited chemotaxis and function of several inflammatory cells involved in asthma pathogenesis, such as eosinophils, and presented an antiremodeling effect in airway epithelial, smooth muscle cells, and fibroblasts in vitro. In addition, both PGE2, 15d-PGJ2, and LXs are able to induce macrophage reprogramming to an alternative M2 pro-resolving phenotype in vitro and in vivo. Although PGE2 and LXA4 showed some beneficial effects in asthmatic patients, there are limitations to their clinical use, since PGE2 caused side effects, while LXA4 presented low stability. Therefore, despite the strong evidence that these AA-derived PRMs induce resolution of both inflammatory response and tissue remodeling in asthma, safer and more stable analogs must be developed for further clinical investigation of their application in asthma treatment.